2021
DOI: 10.3390/pr9050845
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Adhesion between Wet Clay Soil and Rotary Tillage Part in Paddy Field Based on Discrete Element Method

Abstract: To analyze the process of wet clay soil adhering to the rotary tillage part during rotary tillage in paddy field, simulation tests were carried out based on the discrete element method (DEM) in this study. The Plackett-Burman (PB) test was applied to obtain simulation parameters that significantly affected the soil adhesion mass. The Box-Behnken design (BBD) based on the principle of response surface method (RSM) was used to establish a regression model between significant parameters and soil adhesion mass. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…5.6 it follows that a 10% decrease in water content leads to a 0.35 MPa decrease in soil compaction. This can be explained by the increasing fragility of loamy soil due to a decrease in the adhesion of the structural bonds, which was confirmed by previous research (Terfaya et al, 2018;Cheng et al, 2021).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…5.6 it follows that a 10% decrease in water content leads to a 0.35 MPa decrease in soil compaction. This can be explained by the increasing fragility of loamy soil due to a decrease in the adhesion of the structural bonds, which was confirmed by previous research (Terfaya et al, 2018;Cheng et al, 2021).…”
Section: Resultssupporting
confidence: 83%
“…With an increase in water content to 30%, a 0.55 MPa decrease in compaction was observed, which can be explained by a decrease in adhesive bonds due to the substitution of inter-structural bonds with capillary ones. The substitution leads to a decrease in the force of internal friction when shear stresses are applied, as confirmed by Cheng et al (2021) and Nawaz et al (2013). To sum up, the study revealed, that soil, as a porous natural body, has a bearing capacity to support plant life.…”
Section: Resultsmentioning
confidence: 54%
“…By studying the interaction between the rotary blade and the soil, valuable insights can be gained to inform blade design. In a study conducted by Cheng et al [8], the rotary tillage process of a rotary tiller blade was simulated using the discrete element method. The findings indicated that the soil adhesion force primarily accumulates on the oblique long part of the rotary tillage blade.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have explored altering particle trajectories by designing blades of different shapes to influence the movement of soil particles along predetermined paths [12][13][14][15]. Others have investigated the cutting and scattering processes of blades to uncover underlying patterns of particle motion [16][17][18][19][20]. Additionally, computer simulation techniques have been employed by some scholars to establish numerical models simulating blade operation processes [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%